The effectiveness of written emotional disclosure training on psychological well-being and quality of life in psychosomatic disorders - Mahnaz Yazdanfar; Gholamreza Manshaee; Mojgan Agah Herris; Ahmad Alipour; Ahmadali Noorbala (Gonabad University of Medical Sciences, 2015)
The present study intends to increase the psychological well-being and quality of life of the patients and their psychological conditions due to emotional discharge with the written structure in the patients suffering from psychosomatic. After using the comprehensive physiological well-being and quality of life questionnaires, eventually 40 patients who were suffering from psychosomatic disorder were selected from among the patients who had referred to Imam Khomeini hospital in Tehran whose selected by convience sampling and regarding to exclude -include criteria. Then, they formed two groups: experimental and control group, on the random basis. After written emotional expression, the data which had been gathered were analyzed using a covariance analysis statistic test. Findings of this study indicated that the emotional expression made a meaningful decrease in the quality of life, health and physical conditions and so, well-being of the subjects of experimental group compared to control group (P< 0.05). Further, emotional disclosure helps people in improving quality of life, psychological well-being and enhancing health and physical conditions in longtime by dissociating the procedure of inhibiting emotions.